Multi-hazard index for assessing the interaction of post-mining hazards - Al Heib, M.; Velly, N. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
The number of abandoned coal mines is continuously increasing in Europe due to the energy transition. Therefore, post-mining risk assessment and associated management remain crucial for mining authorities, policymakers and planners. The paper presents a new approach to adjusting the level of the single hazards considering the interaction between the post-mining hazards. The value of the adjusted hazard is the product of the level of the initial hazard and the level of interaction of this hazard with another hazard. Based on the number and level of the interaction between hazards, the multi-hazard index (MHI) is a score allowing different regions, sectors, etc. to be compared. The multi-hazard index approach can be used for territories presenting multiple hazards to target areas in which the number of interactions between hazards is significant, considering the level of hazard of each expected phenomenon. It thus makes it possible to prioritise sectors for overall hazard management.